2019
DOI: 10.21608/ejchem.2019.11907.1750
|View full text |Cite
|
Sign up to set email alerts
|

Structure investigation of solid ion pairs of three imidazole drugs-Rose Bengal using different spectroscopic techniques and Their Biological Activities

Abstract: T HE present work is concerned with preparation, separation and structure elucidation of solid ion-pairs of three antifungal drugs Fluconazole (FLZ), Voriconazole (VRZ) and Butoconazole nitrate (BTZ) with Rose Bengal (Rbeng). The solid ion-pairs were prepared and investigated using FT-IR, mass spectral (MS) and thermal analyses (TA), in addition to elemental analysis (EA). The general formulae of the prepared ion-pairs were determined. Moreover, the formulae of prepared ion-pairs were proposed and structurally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The results of the MTT assay of [Cr(CO) 4 L] complex clarified that the free ligand inhibitory potency was slightly decreased by the complexation with Cr(CO) 6 . These results were explained in the same way like that previously published [44][45][46] in research our group.…”
Section: Anticancer Activitysupporting
confidence: 87%
“…The results of the MTT assay of [Cr(CO) 4 L] complex clarified that the free ligand inhibitory potency was slightly decreased by the complexation with Cr(CO) 6 . These results were explained in the same way like that previously published [44][45][46] in research our group.…”
Section: Anticancer Activitysupporting
confidence: 87%
“…This five member organic heterocyclic scaffolds not only finds applications in biological and medicinal field but also finds many applications in analytical and industrial fields [3]. Substituted imidazole derivatives have remarkable binding affinity with various metal ions present in numerous biological active sites and also found to exhibit good inhibitory activities against glucagon receptor antagonists [4], P38 MAP kinaseinhibitors [5], B-Raf kinaseinhibitors [6], etc. (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the low aqueous solubility of the drug could affect its bioavailability and therapeutic performance [ 34 ]. Different research groups reported many complexation studies of the FZ with varying types of naturally occurring and semisynthetic macrocyclic cyclodextrins [ 38 , 48 , 55 , 56 , 57 , 58 ]. Abranches et al [ 34 ] reported a complexation study of FZ with sodium p -sulfonatocalix[ n ]arenes ( n = 4 and 6).…”
Section: Introductionmentioning
confidence: 99%
“…Different research groups reported many complexation studies of the FZ with varying types of naturally occurring and semisynthetic macrocyclic cyclodextrins [38,48,[55][56][57][58]. Abranches et al [34] reported a complexation study of FZ with sodium p-sulfonatocalix[n]arenes (n = 4 and 6).…”
Section: Introductionmentioning
confidence: 99%